ANALYSIS OF VOCATIONAL HIGH SCHOOL TEACHERS` READINESS IN IMPLEMENTING MERDEKA BELAJAR CURRICULUM - Azizah, Anisa Nur; Prastikawati, Entika Fani; Hawa, Faiza (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Merdeka Belajar Curriculum is a new curriculum in Indonesia. For implementing this new curriculum, teachers are require to have readiness. The aim of this study was to analyze the teachers` readiness in implementing Merdeka Belajar Curriculum. This research used descriptive qualitative and the questionnaire as the data collection technique which distributing to twelve of the vocational high school teachers by using Google form. The result showed that on average the teachers were strongly agree with all statements regarding the teachers` readiness to implement Merdeka Belajar curriculum, which consist of five aspects including; the teachers' readiness in implementing Merdeka Belajar Curriculum. The aspects are; the teachers` ability to implement the Merdeka Belajar Curriculum, the ability to construct the lesson plan, the ability to apply the lesson plan based on Merdeka Belajar Curriculum, to conduct assessment based on Merdeka Belajar Curriculum and apply the learning media based on the Information and Communication Technologies (ICT). It indicates that they have readiness in implementing Merdeka Belajar Curriculum by having a good understanding and adequate experiences of Merdeka Belajar Curriculum.